Skim Bantuan Zakat Mualaf: Satu Kajian Kontemporari di Wilayah Persekutuan - Azman Ab Rahman, Irwan , M.S, Mahazan , A.M, Nuradli Ridzwan Shah ,M.D, Wan Mohd. Fazrul Azdi , W.R, Rose Irnawaty Ibrahim, Norlina Ismail (Universiti Sains Islam Malaysia, 2017)
Converts is one of the group which obtained a portion of zakat after asnaf and poor groups and registed zakat collecters (amil). Systematic distribution of zakat can give justice to those who are eligible to receive zakat donations as converts. Majlis Agama Islam Wilayah Persekutuan (MAIWP) as an institution that responsible for managing the zakat fund has provided various aid schemes for them. The question arises whether zakat distribution scheme and aid provided by the MAIWP can meet all the needs and will of converts, especially in the Federal Territory. Therefore, this study was undertaken to determine the distribution of zakat schemes provided to convert by MAIWP. These schemes will be assesed either it is cover convert need by total based on the reality of life, particularly in the Federal Territory of Kuala Lumpur. This study used a qualitative methodology through text study and field studies to reach respondents who are directly involved in managing the distribution of zakat. The study found that the distribution schemes provided by MAIWP nearly complete each conversion needs. The study suggests a number of improvements such as burial scheme, Tabung Haji Savings Scheme and other schemes to meet the needs of life and preserving the welfare of converts. Further studies should be conducted to identify the constraints and needs of converts, especially after the Goods and Service Tax (GST) was implemented to improve existing zakat distribution scheme to convert from time to time.